The Role Of Enterprise Risk Management And Digital Transformation On Sustainable Banking In Indonesia - Indra Saputra; Etty Murwaningsari; Yvonne Augustine (International Publisher (YAPENBI), 2023)
This research investigates the role of Enterprise Risk Management and Digital Transformation in banking sustainability in Indonesia. Banking demands good performance from its owners and shareholders to carry out operational activities on an ongoing basis. In this study, the target population is the Indonesian Banking Sector, which has a digital banking transformation experience. The data was collected by administering questionnaires to the Director/Manager/Division Head/Branch Head of the company. Data were analyzed using descriptive and verification analysis using Partial Least Square (PLS) Structural Equation Modeling (SEM). Additional moderation analysis was also employed to examine the element of mediation. The findings reveal that Enterprises Risk Management and Digital Transformation Banking significantly and positively influence banking sustainability in Indonesia. The Moderation Variable used is that knowledge management cannot improve the relationship between Enterprises Risk Management and Digital Transformation Banking on Banking Sustainability in Indonesia. The issue of sustainability in the financial services involve many aspects; therefore, the key to the sustainability strategy is the awareness from the banking sector of relevant impacts and robust risk management. Technological developments in the banking sector have significant implications for banking which have an impact on corporate survival.